Sexual attractiveness of male chemicals and vocalizations in mice - Asaba, Akari; Hattori, Tatsuya; Mogi, Kazutaka; Kikusui, Takefumi (Frontiers in Neuroscience, 2014)
Male-female interaction is important for finding a suitable mating partner and for ensuring reproductive success. Male sexual signals such as pheromones transmit information and social and sexual status to females, and exert powerful effects on the mate preference and reproductive biology of females. Likewise, male vocalizations are attractive to females and enhance reproductive function in many animals. Interestingly, females’ preference for male pheromones and vocalizations is associated with their genetic background, to avoid inbreeding. Moreover, based on acoustic cues, olfactory signals have significant effects on mate choice in mice, suggesting mate choice involves multisensory integration. In this review, we synopsize the effects of both olfactory and auditory cues on female behavior and neuroendocrine functions. We also discuss how these male signals are integrated and processed in the brain to regulate behavior and reproductive function.